Restricted geographic distribution and low genetic distinctiveness of steppic Crioceris quinquepunctata (Coleoptera: Chrysomelidae) populations in Central East Europe - Mazur, Miłosz; Kubisz, Daniel; Kajtoch, Łukasz (Entomologica Fennica, 2014)
Crioceris quinquepunctata is a European leafbeetle, rare and strictly associated with steppe-like habitats in Central and Eastern Europe. We sampled suitable localities in Central East Europe to determine the current distribution and to verify whether populations isolated by the Carpathian Mountains (within Pannonian and Pontic area) show genetic differentiation. Sequences from the beetle COI and ITSl were amplified and compared. Furthermore, ftsZ and hcpA genes of the endosymbiont Wolbachia were analysed as additional genetic markers. We found only two populations of C. quinquepunctata (in Moravia and Podolian Upland). Unusually low genetic differences between these populations were revealed, which is in contrast to previous studies on other steppe beetles. The reasons for such low diversity are speculative and probably related to recent natural expansion or man-made translocation of C. quinquepunctata.